EDMODO IN THE CLASS: THE USE OF ONLINE LEARNING IN THE CLASS SEEN FROM STUDENTS' VOICE - Mahendra Puji Permana Aji; Suhartono Suhartono (Universitas Ahmad Dahlan)
Online learning has been main concern in today’s teaching learning process since the rising use of internet. It offers many variant activities and it becomes new alternative way to communicate among teacher and students. Recently students and teachers are expected to have decent knowledge in digital learning as one way to facilitate their learning process. One form of digital learning is using Edmodo in the class. The e-learning model using edmodo was developed to support teaching and learning process in University of Nusantara PGRI Kediri. This media offers an authentic material that can be accessed anytime and anywhere. This model also gives the external links to get the other resources in the World Wide Web. The external links given is related to a discussion topic or material, and it is to improve the students' knowledge and skill in teaching and learning. Because this media is a e-learning model, the students enjoy when they browse and take a look into the material provided. Some of researchers have done the research on it, yet these studies mostly focus on the teachers’ perception towards its application in their classes. This study is a bit different as it is concentrated on students’ perceptions or voice towards Edmodo application in the class. The aim of this study is to explore students’ perception or students’ voice on online learning particularly Edmodo application in class.